(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
The aim of the present study is to introduce a school which can be found in the Krishna valley in Somogyvámos. The Krishna minded people settled down here more than twenty years ago and they have been operating a school and and a kindergarten as well since then. The school fits into the so called traditional Hungarian school system and it is categorized as an ecclesiastical educational institution, but due to its organization and teaching methods it is similar to alternative schools in several ways. As there is no written document about this young school, the present study would like to introduce it to the public for the first time.